1965
DOI: 10.1515/mamm.1965.29.4.517
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Des Mouffettes Andines Au Venin De Serpent

Abstract: La ^sistance de Conepatus rex, mouffette andine d'altitude, est comparable a celle de C. inca dej etudioe, et presque aussi forte que celle des mouffcttes et des sarigues des regions tropicales basses vis-a-vis des Crotalinos amcricains, bien que ceux-ci ne vivent pas a ces hauteurs. Par contre le serum de C. rex et inca ne possede pas de pouvoir protecteur. Les mouffettes ont une resistance nulle aux venins asiatiques de Naja.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…After several components are synthesized and the cytoplasm is enriched in products, the cell membrane ruptures and releases its contents into the venom gland. Although being a rather destructive mode of secretion, holocrine mechanisms have been reported for several spider venom systems [ 6 , 13 , 14 , 50 ]. As it is also encountered in scorpions, holocrine secretion may play a general role in arachnids [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…After several components are synthesized and the cytoplasm is enriched in products, the cell membrane ruptures and releases its contents into the venom gland. Although being a rather destructive mode of secretion, holocrine mechanisms have been reported for several spider venom systems [ 6 , 13 , 14 , 50 ]. As it is also encountered in scorpions, holocrine secretion may play a general role in arachnids [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to the locations and infrequency of reports, it appears brown widows are being introduced multiple times in the Paraguay.-Pickard-Cambridge (1902) mentioned examining brown widow specimens from Paraguay, but locale and collection date were not reported. Badcock (1932) reported brown widows in 1926 (see report from Brazil above) and Vellard (1936) reported them several years later, though specific locations were not reported for either record. There are four records from 2015 in the department of Central (GBIF 2022).…”
Section: Spatiotemporal Patterns Of Brown Widow Introductionsmentioning
confidence: 99%
“…In Brazil, the diet of the brown widow consisted of six arthropod orders with Coleoptera representing 48% and Diptera representing 34% of their prey (Rossi & Godoy 2005). Though not a main portion of their diet, brown widows are also regularly seen feeding upon other arachnids (Vellard 1936). In Brazil, a brown widow was observed preying upon a native black-headed snake (Tantilla melanocephala) that was more than 18 times larger than the spider (Rocha et al 2017), and in Mexico a brown widow was observed feeding on a non-native house gecko (Hemidactylus frenatus) (Luna et al 2020).…”
Section: Spatiotemporal Patterns Of Brown Widow Introductionsmentioning
confidence: 99%